Do the torso muscles produce torso twist in front crawl? - Andersen, J. T.; Sinclair, P.; Fernandes, R.; Vilas-Boas, J. P.; Sanders, R. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of this study was to investigate the association between torso muscle activity and torso twist. EMG data from five torso muscles and 3D motion capture data were recorded during 4x25m front crawl swimming trials at 400m and 50m pace (N=15). EMG data were integrated over 10ms intervals and normalized to the maximum value during each swimming trial (%iEMG) and torso twist acceleration was calculated as the second time derivative of the relative angle between thorax and pelvis about the longitudinal axis. Spearman correlations were calculated between 5th percentile scores of %iEMG and torso twist acceleration. Mean correlation coefficients were weak (i.e. r < 0.30) for all muscles at both paces. The findings suggest that torso muscle activity may not be directly associated with torso twist acceleration.